(Em)Powering the end of power: HRI for safe nuclear decommissioning - Oostveen, Anne-Marie; Zhang, Jingyi; Fletcher, Sarah (Association for Computing Machinery (ACM), 2026)
As fusion research facilities like the Joint European Torus reach the end of their operational lives, the need for safe and precise decommissioning has become critical. Human-Robot Interaction (HRI) technologies are central to reducing human risk and enabling complex remote operations in hazardous environments. Based on an exploratory study with experts from the UK Atomic Energy Authority and the International Thermonuclear Experimental Reactor, this paper examines current and emerging uses of teleoperated manipulators, articulated booms, virtual reality, and force feedback systems in fusion decommissioning. The findings highlight key insights into training, cognitive load, and ethical considerations in operator data use. HRI emerges not just as a technical solution but as a vital enabler for empowering society to transition responsibly away from legacy energy infrastructures.
Keywords: 46 Information and Computing Sciences; 4608 Human-Centred Computing; 7 Affordable and Clean Energy